2001
DOI: 10.1097/00042560-200103010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Molecular Epidemiology of HIV-1 Infection in Taiwan From 1988 to 1998

Abstract: Eight hundred and seventy-nine HIV-1-infected patients (comprising 46% of reported HIV-1/AIDS cases in Taiwan) were recruited for this study of the molecular epidemiology of HIV-1 in Taiwan from 1988 to 1998. HIV-1 subtypes were determined using a modified peptide-enzyme immunoassay complemented with DNA sequencing and phylogenetic analysis. Of the 807 HIV-1 infected men, 68.2% were infected with HIV-1B, 29.5% with HIV-1 circulating recombinant form (CRF)01_AE and 2.3% with other subtypes. Of the 72 HIV-1-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, we found that 97.9% of all infections were caused by subtype B. This was not surprising given that previous reports had already established B as the most predominant subtype among Taiwanese MSM [ 14 , 37 , 38 ]. Of the non-subtype B infections, 2% was attributed to CRF01_AE.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, we found that 97.9% of all infections were caused by subtype B. This was not surprising given that previous reports had already established B as the most predominant subtype among Taiwanese MSM [ 14 , 37 , 38 ]. Of the non-subtype B infections, 2% was attributed to CRF01_AE.…”
Section: Discussionsupporting
confidence: 72%
“…Risk factor analyses showed that more than 50% of the HIV-1/AIDS patients were men who have sex with men (MSM) and about 25% were injection drug users (IDUs) [5] . In terms of subtype distribution, subtype B, CRF01_AE and CRF07_BC were predominant in MSM, heterosexuals, and IDUs respectively [6] [10] . There are an estimated 60,000 to 100,000 IDUs in Taiwan and about 15% of them are infected with HIV-1 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we also discovered that local HIV-1 strains had significant env sequence correlations with Thailand and Hong Kong strains, suggesting that HIV-1 may be transmitted through factors such as tourism and business events, and indirectly transmitted to the Taiwanese MSM population. In addition, from past observations, the dominantHIV-1 subtype of the MSM population in Taiwan is subtype B [21, 22]. The dominant HIV-1 subtype of sex workers, prostitute customers, and heterosexual populations is CRF01_AE.…”
Section: Discussionmentioning
confidence: 97%